Performance of fly ash based geopolymer concrete at high temperature - Suhaimi , Ahmad (2013)
Nowadays the demand for cement concrete based on Portland cement as a construction material is on the increase day by day. The demand of concrete would increase in the future due to increase in infrastructure developments. The production of Portland cement will produce CO 2 gases that release to the atmosphere which causing the global warming of the earth. The new material that calls fly ash based geopolymer concrete which does not need Portland cement as a binder. The Portland cement is replaced by fly ash that rich with silica and alumina. Because the ceramic—like properties of the geopolymer it believed that can provide good fire resistance. This paper is show the result of study on the performance of fly ash based geopolymer concrete when expose to high temperature in term of compressive strength and their porosity. Sodium silicate (Na2 SiO 3 ) and sodium hydroxide (NaOH) solution is act as an activator solution in the fly ash based geopolymer concrete. Concrete sample were cured in the oven at 60°C for 24 hours. After curing the sample were placed at room temperature until test on day 1 day 7 and day 28 for the control. For the research sample it will expose to the difference temperature (100°C, 200°C, 300°C, and 400°C) and difference time (15 minutes, 30 minutes and 60 minutes) at day 28 before testing is conducted. From the research, sample geopolymer concrete was exposed to temperature have high minutes, 45 compressive strength. Porosity result has shown the different trend from the usual result of porosity. The value of porosity is higher when exposed where the compressive strength also higher. Keywords: Geopolymer, Fly ash, elevated temperature, strength, aggregate, concrete